Effects of chicken hemoglobin antimicrobial peptides on intestinal mucosal immunity under chronic heat stress and vaccination responses in broilers - Wang, Decheng; Hu, Fengjiao; Liu, Hui; She, Ruiping; Tian, Jijing (Frontiers in Veterinary Science, 2025)
Heat stress (HS) is a major concern in poultry production worldwide due to its adverse effects on feed intake, weight gain, carcass weight, and metabolic conditions. Several strategies have been explored to ameliorate the negative effects of HS in broiler chickens, among which antimicrobial peptides (AMPs) represent a promising approach. Previously, we isolated chicken hemoglobin antimicrobial peptides (CHAP) and further demonstrated that CHAP has strong bactericidal activity. However, whether CHAP can improve growth performance and maintain intestinal mucosal immunity under chronic HS conditions remains unclear. In the present study, a total of 141 one-day-old broilers were divided into two groups. A total of 36 broilers were used to establish a chronic HS model to evaluate the effects of CHAP on intestinal mucosal immunity, and the remaining 105 birds were used to monitor the inductive effects of CHAP on two vaccines, including Newcastle disease virus (NDV) and avian influenza virus (AIV) vaccines, in broilers. As expected, HS-stimulated broiler chickens supplemented with CHAP showed a significant increase in villus height in the duodenum (p < 0.01), jejunum (p < 0.05), and ileum (p < 0.01) compared to those who did not receive CHAP under chronic HS conditions. The levels of alkaline phosphatase (AKP) and the number of secretory IgA (sIgA)-producing cells were markedly decreased in the chronic HS group (p < 0.01), whereas both significantly recovered after CHAP administration (p < 0.01). CHAP administration improved the birds' body weight and average daily gain (ADG), as well as the feed utilization rate, under HS conditions. Moreover, CHAP effectively mitigated HS-induced bursa injury by inhibiting excessive bursal apoptosis through the downregulation of caspase-3 and Bax, as well as the upregulation of Bcl-2 (p < 0.01). Interestingly, CHAP supplementation enhanced the antibody titer of both NDV and AIV in the broilers. Finally, CHAP administration enhanced the proliferation of splenic lymphocytes. In summary, our data demonstrate that CHAP not only maintains intestinal stability to improve growth performance but also inhibits excessive apoptosis in immune organs and upregulates vaccination effects.